ANALYSIS OF SERVICE QUALITY ON THE LEVEL OF SERVICE USER SATISFACTION USING THE SERVQUAL METHOD AT THE BAII ISLAND FERRY PORT, BENGKULU PROVINCE - Priyono, Broto; Diani, Oktrianti; Satrio, Seto (IWTJ : International Water Transport Journal, 2025)
ASDP Indonesia Ferry (Persero) Padang Branch, is the manager of the Baai Island – Kahyapu ferry port. Based on the results of field observations, it was found that several services for service users have not been carried out properly, such as not having evacuation route instructions and evacuation gathering points, prayer rooms whose areas are still not clean and prayer equipment is not available, passenger waiting rooms do not have air conditioning which causes hot temperatures in the waiting room. In this study, the method used to analyze existing problems is the Gap Service Quality method to determine the gap between service user perceptions of the quality of service provided by the port and service user expectations of Port services and mapping the Importance Performance Analysis quadrant to determine the attributes that are the main priority in improving the quality of Port services. In the calculation of the Gap Service Quality analysis, the highest Gap value was obtained for services in the tangibles dimension with a value of -2.37 on attribute 7, the reliability dimension with a value of -0.59 on attribute 13, the responsiveness dimension with a value of -0.59 on attribute 18, the assurance dimension with a value of -2.04 on attribute 22, the Empathy dimension with a value of -0.56 on attribute 26, and the average value of the gap for all dimensions was -0.93. So what was obtained from the calculation of the service quality gap showed a negative result <0 which indicated that the service was less than satisfactory. Based on the results of the Importance Performance Analysis quadrant mapping analysis, there were 12 attributes in quadrant I as the main priority for improvement so that the level of service user satisfaction could increase.